Inclusive Management Through Gender Consideration in Small-Scale Fisheries: The Why and the How - de la Torre-Castro, Maricela (Frontiers in Marine Science, 2019)
In a world in which ocean degradation is widespread and aggravated by the effects of climate change, there is a need to contribute with new management approaches to ameliorate the situation. Here, inclusive management is proposed as such an alternative. This contribution argues that including all genders in the management process is needed and the inclusion itself can generate new ways to solve problems. An assessment of findings from literature of the positive aspects when considering gender in environmental governance is presented and related to the specific situation of small-scale fisheries (SSF). These positive findings are explained in terms of 1) Participation, 2) Space, actors and activities, 3) Economic power, and 4) Equity and environmental stewardship. Further, a practical approach is taken and a model for gender inclusion in coastal/ocean management for SSF is presented and illustrated with a case of seagrass SSF in East Africa. The central argument is that in view of ongoing coastal/ocean degradation and the moderate governance and management success, it is worth trying management approaches that consciously and explicitly consider gender and diversity of actors. This will bring central actors (e.g. women not previously considered) into the management process and will provide the base for better governance and policy reform.